Construction of neural system disease models from the perspective of cellular biomechanics and their application in teaching practice - Xue, Hong; Zhao, Qiong; Zhao, Zhilan; Li, Ruozhao; Li, Guangyu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundNeurological diseases such as Alzheimer’s, Parkinson’s, and multiple sclerosis present significant challenges to healthcare systems due to their complex pathophysiological mechanisms. Recent advancements in cellular biomechanics have opened new avenues for modeling these diseases, providing insights into how mechanical forces influence cellular behavior and contribute to disease progression.MethodsThis study explores the construction of neurological disease models from a cellular biomechanics perspective and their integration into educational practices. We combined biomechanical principles with traditional biological models to develop multiscale representations of neurological disorders, encompassing cellular, tissue, and organ levels. The models were applied in teaching through the design of interactive scenarios, including virtual simulations and 3D-printed anatomical structures, to promote active student engagement.ResultsThe integration of biomechanical models enhanced the understanding of disease mechanisms and facilitated the identification of key intervention targets. Teaching strategies incorporating these models improved student comprehension of neurological diseases, as evidenced by evaluation outcomes. The models also supported the development of personalized rehabilitation programs, demonstrating potential for clinical translation.ConclusionThe application of cellular biomechanics in neurological disease modeling enriches both research and educational practices. By bridging biomechanical insights with clinical and teaching applications, this approach prepares future healthcare professionals to address complex neurological disorders more effectively. Interdisciplinary collaboration among biomechanics, education, and clinical medicine is essential to advance neurological rehabilitation and improve patient outcomes.